The Unveiling the Faces of Corruption in Education: A Systematic Review of Various Forms of Corruption across Countries and Educational Levels - As Sayfullooh, Istiqomah; Rusdinal, Rusdinal; Hadiyanto, Hadiyanto; Olivia, Nesta; Marhadi, Agung (Acta Paedagogica Vilnensia, 2024)
In recent years, researchers have paid close attention to educational corruption. While numerous studies have investigated various forms of corruption in education, there has been a dearth of research that spans a wide range of countries and educational levels. Based on the findings of the previous decade, this study attempted to fill this research gap by undertaking a systematic review of various forms of corruption in education across countries and educational levels. Using a systematic literature review technique, this study assessed the prevalence of various forms of corruption in education, with a focus on bribery as the most commonly reported form across coutries. Furthermore, it showed that higher education institutions gained greater research focus regarding corruption and exhibited a diverse variety of corrupt activities compared to primary and secondary education. This review emphasised the significance of future research on corruption in elementary and secondary education, particularly on types of corruption other than bribery and mutually beneficial connections. This study contributed to the existing literature by enhancing our understanding of the many types of corruption in education and their prevalence across countries and educational levels. It also provided policymakers and educators with insights into how to establish effective tactics for eliminating corruption in education systems.